1983
DOI: 10.4315/0362-028x-46.12.1036
|View full text |Cite
|
Sign up to set email alerts
|

Cook/Chill Foodservice Systems: Microbiological Quality and End-Point Temperature of Beef Loaf, Peas and Potatoes After Reheating by Conduction, Convection and Microwave Radiation,

Abstract: Microbiological quality, as estimated from temperature and mesophilic aerobic plate counts of beef loaf, instant mashed potatoes and frozen peas, was determined at point of service to compare conduction, convection and microwave reheating in a hospital-type cook/chill foodservice system. Although reheated products were similar microbiologically (mean log CFU/g = 2.3 to 3.4), internal end temperatures, even under laboratory-controlled conditions, did not meet FDA recommended standards (≥74°C) for reheated produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…However, the highest percentage of food samples positive for S. ~~h i~~r i u m was presented by foods that achieved the highest temperatures (Tables 2 and 3). In relation to minimum and maximum end-point temperatures, our results agree with those of Sawyer et al (1983) who also observed different temperatures in different portions of food with the same weight and similar shape.…”
Section: Resultssupporting
confidence: 91%
“…However, the highest percentage of food samples positive for S. ~~h i~~r i u m was presented by foods that achieved the highest temperatures (Tables 2 and 3). In relation to minimum and maximum end-point temperatures, our results agree with those of Sawyer et al (1983) who also observed different temperatures in different portions of food with the same weight and similar shape.…”
Section: Resultssupporting
confidence: 91%
“…Limiting factors for the conventional cook-chill process include those relating to shelf-life (Schafheitle & Light, 1989), microbiological safety (Sawyer et al , 1983;Snyder & Matthews, 1984;Sheard, 1988;Trollope & Helby, 1989) and nutritive value (Bognar, 1980;Hunt, 1984). Two of these limitations are addressed in an extension of the process by the introduction of an additional stage, either prior to or immediately following 'full cooking' (pasteurization), in which the product is placed in an impermeable plastic laminate pouch which is then evacuated and sealed.…”
Section: Introductionmentioning
confidence: 99%